Hot High-Mass Accretion Disk Candidates - Beuther, H.; Walsh, Andrew; Longmore, S. (Institute of Physics Publishing, Inc., 2009)
To better understand the physical properties of accretion disks in high-mass star formation, we present a study of a dozen high-mass accretion disk candidates observed at high spatial resolution with the Australia Telescope Compact Array (ATCA) in the high-excitation (4,4) and (5,5) lines of NH3. All of our originally selected sources were detected in both NH3 transitions, directly associated with CH3OH Class II maser emission and implying that high-excitation NH3 lines are good tracers of the dense gas components in hot-core-type targets. Only the one source that did not satisfy the initial selection criteria remained undetected. From the 11 mapped sources, six show clear signatures of rotation and/or infall motions. These signatures vary from velocity gradients perpendicular to the outflows, to infall signatures in absorption against ultracompact H II regions, to more spherical infall signatures in emission. Although our spatial resolution is ~1000 AU, we do not find clear Keplerian signatures in any of the sources. Furthermore, we also do not find flattened structures. In contrast to this, in several of the sources with rotational signatures, the spatial structure is approximately spherical with sizes exceeding 104 AU, showing considerable clumpy sub-structure at even smaller scales. This implies that on average typical Keplerian accretion disks—if they exist as expected—should be confined to regions usually smaller than 1000 AU. It is likely that these disks are fed by the larger-scale rotating envelope structure we observe here. Furthermore, we do detect 1.25 cm continuum emission in most fields of view. While in some cases weak cm continuum emission is associated with our targets, more typically larger-scale H II regions are seen offset more than 10'' from our sources. While these H II regions are unlikely to be directly related to the target regions, this spatial association nevertheless additionally stresses that high-mass star formation rarely proceeds in an isolated fashion but in a clustered mode.